The Role of Female Principal Leadership in Enhancing Teacher Performance at Jasinga Elementary Schools - Basri Asyibli; Apud Apud; Uyu Muawanah; Yahdinil Firda Nadhira; Imas Mastoah (UIN Sultan Aji Muhammad Idris Samarinda, 2026)
The rising number of female principals in Indonesian elementary schools has not yet been matched by equitable teacher performance, especially in rural”‘suburban areas such as Jasinga. This study analyzes how female principal leadership enhances teacher performance in three public elementary schools in Jasinga District, namely SDN Jasinga 03, SDN Jasinga 06, and SDN Jasinga 07. A qualitative multiple case study design was used, involving three female principals, nine teachers, and three education staff selected purposively. Data were collected through observation, semi”‘structured interviews, and document analysis, then analyzed using interactive qualitative procedures of data reduction, display, and conclusion drawing. The findings show that female principals improve teacher performance through openness, empathy, assertiveness, responsibility, inspirational role-modelling, and participatory communication, which are implemented in professional development programs, Merdeka Curriculum workshops, MGMP activities, structured academic supervision, and continuous performance evaluation. The study concludes that female principal leadership is effective and strategic in strengthening teacher performance in planning, implementing, and evaluating learning in rural”‘suburban public elementary schools, and recommends ongoing leadership development, institutional support for teacher learning communities, and further comparative or mixed”‘methods research on gendered educational leadership in Indonesia. Keywords: female principal leadership, gender leadership in education, principal leadership, public elementary schools, teacher performance